Legal Regulation of Territorial Defense of Ukraine and the Place of Administrative Legislation in it - Rusetskyi, Anatolii Anatoliiovych; Lelet, Serhii Mykolaiovych; Dopilka, Vladyslav Oleksiiovych; Tsybulnyk, Nelli Yuriivna (Fakultas Syariah dan Hukum, UIN Syarif Hidayatullah Jakarta, 2020)
AbstractThe purpose of this article is to study the specifics, and characteristics of administrative and legal regulations of the territorial defense system of Ukraine, as well as to find the optimal model of legislative changes in the field. While writing the article the following methods were used: dialectical, logical-semantic, comparative-legal, analysis and synthesis. The issues of administrative and legal regulations of territorial defense of Ukraine, as well as the peculiarities of its legislative support is considered in the article. The author's definition of the concepts “territorial defense of Ukraine” and “administrative and legal regulation” is formed and provided with the help of the analysis of scientific views. In accordance with the subject of the article, the characteristics of the practical implementation of defense policy by special public authorities, as well as the implementation of measures of administrative and legal regulations in relation to the implementation of defense measures is defined. Proposals to improve certain procedures for the introduction, and implementation of professional activities of defense policy entities and control over it are provided, as well as the importance of effective administrative and legal support of their daily lives in the course of their duties is stressed. It is proposed to amend the relevant legislation to improve the quality of effective activities of domestic defense structures, improve the system of motivational and incentive methods that can be used to defend the Ukrainian border and domestic administrative-territorial units.Keywords: Administrative and Legal Regulation, Territorial Defense and Legislative Support, State Bodies, Combat Units, International Cooperation. Abstrak:Tujuan artikel ini adalah untuk mempelajari kekhususan dan karakteristik regulasi administratif dan hukum sistem pertahanan teritorial Ukraina, serta untuk menemukan model optimal dari perubahan legislatif di lapangan. Penulisan artikel ini menggunakan metode: dialektika, logis-semantik, perbandingan-hukum, analisis dan sintesis. Masalah regulasi administratif dan hukum pertahanan teritorial Ukraina, serta kekhasan dukungan legislatifnya dipertimbangkan dalam artikel tersebut. Definisi penulis tentang konsep